Selective inhibition of TGF-β1 produced by GARP-expressing Tregs overcomes resistance to PD-1/PD-L1 blockade in cancer - Grégoire de Streel (Nature Portfolio, 2020)
Inhibiting TGF-β1 to increase immune responses against tumors bears the risk of tumor-promoting toxicity. Here the authors show that selectively blocking TGF-β1 produced by immunosuppressive cells is feasible with anti-GARP:TGF-β1 antibodies and improves the efficacy of PD-1 blockade immunotherapy.